A Study on the Winning Steps Maybank Undertake to Gain and Sustain Customers - Rajesh Kumar Nair; Varsha Ganatra; Ooi Tian Xiang; Daisy Mui Hung Kee; Ooi Pei Ying; Teh Jing Xuan; Tan Sia Ling; Priyanka Sebastian; Uma Warrier; Amol Sanjay Karkare; Rupesh Sinha; Dian Pratama; A.A. Gde Satia Utama; Vinay Mehta (Global Academia Publisher, 2020)
This study focuses on customer satisfaction factors. The purpose of this study is to examine the significant factors of the bank that can influence the satisfaction level of the customer. This study also presents how customers rate the factors according to their preferences and demographic factors. Maybank is the largest financial services group and the leading banking group in South East Asia. The goal of Maybank is to humanize financial services across Asia by providing people with access to financial services at reasonable terms and rates and to always be at the heart of the community.